Effects of information provision on public attitudes toward bioplastics in Japan - Otaki, Yurina; Kyono, Taisei (Frontiers in Sustainability, 2022)
Bioplastics (i.e., bio-based and biodegradable plastics) are attracting attention as a sustainable alternative to conventional fossil-based plastics. However, their use in Japan, the fifth-highest per capita disposal of single-use plastics, has not become as widespread as planned by the Japanese government, and an increase in consumer awareness is necessary to promote the use of bioplastics and increase the demand for sustainable products. In addition, to promote social implementation, it is also necessary to understand the difference between bio-based and biodegradable plastics and use them correctly. Through an online questionnaire survey, this study found that the Japanese public’s knowledge of bioplastics was low: there was a major difference between subjective and objective knowledge, but their perception of bioplastics was more positive than that of conventional plastics. However, they had little experience in using bioplastics. Therefore, we investigated whether providing information would promote the intent to use bioplastics. As a result, information provision is likely to be effective in increasing the willingness to use bioplastics in addition to promoting positive perceptions. The participants indicated a significantly greater willingness to pay a higher price for single-use plastics (such as a 500 ml bottle of water), but not for durable plastics (such as a three-color ballpoint pen).